Galectin 3‐binding protein (LGALS3BP) depletion attenuates hepatic fibrosis by reducing transforming growth factor‐β1 (TGF‐β1) availability and inhibits hepatocarcinogenesis - Dae‐Hwan Kim; Minjeong Sung; Myong‐Suk Park; Eun‐Gene Sun; Sumin Yoon; Kyung Hyun Yoo; Kamalakannan Radhakrishnan; Sung Yun Jung; Woo‐Kyun Bae; Sang‐Hee Cho; Ik‐Joo Chung (Cancer Communications, 2024)
Abstract Background Increased Galectin 3‐binding protein (LGALS3BP) serum levels have been used to assess hepatic fibrosis stages and the severity of hepatocellular carcinoma (HCC). Considering the crucial role of transforming growth factor‐β1 (TGF‐β1) in the emergence of these diseases, the present study tested the hypothesis that LGALS3BP regulates the TGF‐β1 signaling pathway. Methods The expression levels of LGALS3BP and TGFB1 were analyzed in patients with metabolic dysfunction‐associated steatohepatitis (MASH) and HCC. Multiple omics techniques, such as RNA‐sequencing, transposase‐accessible chromatin‐sequencing assay, and liquid chromatography‐tandem mass spectrometry proteomics, were used to identify the regulatory mechanisms for the LGALS3BP‐TGF‐β1 axis. The effects of altered TGF‐β1 signaling by LGALS3BP were investigated in conditional LGALS3BP‐knockin and LGALS3BP‐knockout mice. Results In patients with MASH and HCC, the levels of LGALS3BP and TGFB1 exhibited positive correlations. Stimulation of LGALS3BP by the inflammatory cytokine interferon α in HCC cells or ectopic overexpression of LGALS3BP in hepatocytes promoted the expression levels of TGFB1. Aggravated fibrosis was observed in the livers of hepatocyte‐specific LGALS3BP‐knockin mice, with increased TGFB1 levels. LGALS3BP directly bound to and assembled integrin αV, an integral mediator required for releasing active TGF‐β1 from extracellular latent complex with the rearranged F‐actin cytoskeleton. The released TGF‐β1 activated JunB transcription factor, which in turn promoted the TGF‐β1 positive feedback loop. LGALS3BP deletion in the hepatocytes downregulated TGF‐β1 signaling and CCl4 induced fibrosis. Moreover, LGALS3BP depletion hindered hepatocarcinogenesis by limiting the availability of fibrogenic TGF‐β1. Conclusion LGALS3BP plays a crucial role in hepatic fibrosis and carcinogenesis by controlling the TGF‐β1 signaling pathway, making it a promising therapeutic target in TGF‐β1‐related diseases.